Web-Based Document Archiving Information System In Commission C DPRD Of North Sumatra Province - Syamia, Nanda; Lubis, Amalina Shadrina; Nur Hera Zabni; Rifqi, Mhd Ikhsan (SAINTEKBU, 2024)
Commission C DPRD of North Sumatra Province is a commission that operates in the financial sector. In Commission C DPRD, the relationship between the budget and documents is closely related because documents are often used as a tool to record, track and present financial information. These documents assist Commission C in monitoring, evaluating and making decisions related to regional financial management. The document is an important reference to ensure transparency, accountability and efficiency of budget management in accordance with policies and community needs. The existence of documents is usually important because they record or record information that can be accessed and used as a reference in the future. Document management within Commission C DPRD of North Sumatra province still faces several obstacles, including manual processes that are vulnerable to human error, the time required to search for documents, and the risk of document loss or damage. Seeing this problem, a new system is needed that utilizes technology in the current era to deal with several obstacles related to document management. The aim is to design and implement a web-based document archiving information system at Commission C DPRD of North Sumatra province to increase efficiency, security and readability of information in document management. The research methods used in this study are Research and Development. Research and Development Research and development (R&D). This system was built by modeling several UML diagrams such as use case diagrams, activity diagrams, and class diagrams. It is hoped that Commission C DPRD of North Sumatra province can optimize document management performance and make a positive contribution to improving service quality and transparency within this institution.